Factors Influencing Customers on the Use of E-Payment in Klang Valley - Ramli, Atiqah Akmal; Mazlan, Nur Izzati binti; Harun, Zatul Fahany; Mohd Yusof, Yuslina Liza Bte (Information Management and Business Review, 2024)
The adoption of electronic payment systems (e-payments) has gained significant traction worldwide. E-payment systems have become widely accepted and used in Malaysia’s Klang Valley area. The purpose of this study is to investigate the elements that drive customer acceptance of e-payment systems in the Klang Valley, with emphasis on convenience, security, speed and social influence. Drawing upon existing literature, convenience emerges as a critical determinant of e-payment adoption. Security considerations also play a crucial role, as consumers prioritize platforms with robust security measures. Additionally, the speed of transactions is a significant factor influencing consumers’ preferences with faster processing times. Furthermore, social influence, encompassing peer recommendations and societal norms, shapes consumers’ attitudes and behaviors toward e-payment adoption. To empirically test these factors, a quantitative research methodology will be employed, with data collected through non-probability sampling techniques. The study will focus on people of the Klang Valley, especially Kuala Lumpur, who use electronic payment methods. The data will be analyzed and validated using descriptive analysis, reliability tests, Pearson correlation coefficient, and multiple regression analysis. This study’s findings are likely to give useful insights for policymakers, industry stakeholders and researchers looking to encourage the acceptance and use of e-payment systems. Understanding the elements that influence customers’ attitudes and behaviors toward e-payment adoption allows for the development of targeted strategies to improve the accessibility, security, and efficiency of digital payment systems. Finally, this study hopes to contribute to the promotion of financial inclusion and the growth of the digital economy.